Efficacy and safety of Gemogenovatucel-T (Vigil) immunotherapy for advanced ovarian carcinoma: A systematic review and meta-analysis of randomized controlled trials - Zhang, Yixin; Zhang, Li; Zhao, Yuli; Wang, Sen; Feng, Li (Frontiers in Oncology, 2022)
In recent years, many clinical trials have shown the safety and efficacy of Gemogenovatucel-T (Vigil) in the treatment of advanced OC patients. The purpose of this study was to explore the safety and efficacy of Gemogenovatucel-T (Vigil) in the first-line maintenance of advanced ovarian carcinoma based on the randomized controlled trials (RCTs). Randomized controlled trials (RCTs) on Gemogenovatucel-T (Vigil) immunotherapy for advanced ovarian carcinoma were searched in PubMed, Embase, Cochrane Library and Web of Science up to December 31, 2021. The following study characteristics were investigated: baseline study characteristics, overall survival, recurrence free survival, recurrence free survival median time, and complication. A total of 36 articles were obtained, and seven suitable RCTs with a total sample size of 322 patients were eventually included in this meta-analysis. Overall survival (OS): from time of randomization: HR=0.48 (95% CI: 0.32 to 0.72), Z=3.55, P<0.001; from time of tissue procurement: HR=0.51 (95% CI: 0.33 to 0.78), Z=3.07, P=0.002. Recurrence free survival (RFS): from time of randomization: HR=0.43 (95% CI: 0.30 to 0.62), Z=4.61, P<0.001; from time of tissue procurement: HR=0.45 (95% CI: 0.31 to 0.65), Z=4.26, P<0.001. RFS median time: from time of randomization: HR=1.57 (95% CI: 1.16 to 2.11), Z=2.95, P=0.003; from time of tissue procurement: HR=2.16 (95% CI: 1.12 to 4.17), Z=2.29, P=0.022. This study found that Gemogenovatucel-T (Vigil) immunotherapy provided significant OS and RFS benefits, particularly in advanced OC patients with BRCA wild type. At the same time, treatment with the Gemogenovatucel-T (Vigil) is safer than other treatment modalities and does not have any toxic effects.